THE THEORY OF THE SOCIAL CONTRACT AND THE LEGITIMIZATION OF CRIMINAL LAW - Qurbonov Doniyorbek Davlatovich (Scholar Express Journals, 2024)
The paper is devoted to one of the most fundamental problems of criminal law – its legitimation. Researchers do not pay enough attention to this problem, which leads to the unsystematic use of criminal law tools and reduces the efficiency of the whole branch of law. The object of this work is the views of various philosophical, sociological and legal schools on the substantiation of state violence; the sources of pre-revolutionary, Soviet criminal law; active Russian and foreign legislation; pre-revolutionary and modern works on the theory of criminal law. The goal of the author is to work out a holistic and consistent approach to this problem. He summarizes and systematizes research ideas that are analyzed with the help of philosophical theories and active Russian and foreign legislation. The author concludes that the most prospective direction of legitimation of criminal law is the substantiation of state violence on the basis of the theory of social contract. Its advantage is that it is based on the balance between the sovereignty of the person and the interests of safety. The author believes that the natural consequence of this theory is the conceptualization of criminal law as an extreme measure of counteracting infringements. The author examines some general aspects of the introduction to criminal law from the standpoint of social contract. He also substantiates the existence of criminal law relations before socially dangerous acts are committed and argues that the all members of a society are participating in these criminal law relations. The main task of criminal law is the protection of social relations. The obtained results can be used in law enforcement, in teaching criminal law disciplines and in the further research of the problems of introduction to the criminal law.
Keywords: Termin; criminal law; essence of criminal law; object